Erratum to expanded criteria for active surveillance in prostate cancer: a review of the current data - Jones, Cameron; Fam, Mina M.; Davies, Benjamin J. (Translational Andrology and Urology, 2018)
Erratum to: Transl Androl Urol 2018;7:221-7.